2009
DOI: 10.1590/s1414-98932009000200013
|View full text |Cite
|
Sign up to set email alerts
|

Envolvimento religioso e bem-estar subjetivo em idosos

Abstract: As inter-relações do envolvimento religioso com o bem-estar subjetivo em idosos foram investigadas neste trabalho. Participaram da pesquisa 256 indivíduos de ambos os sexos, com idades variando de 60 a 90 anos, que responderam a três instrumentos destinados a mensurar sua satisfação com a vida, seus afetos positivos e negativos e seu envolvimento religioso bem como a perguntas de natureza sociodemográfica. Os resultados evidenciaram que, dentre as dimensões do envolvimento religioso, apenas a religiosidade sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
(22 reference statements)
0
9
0
17
Order By: Relevance
“…For the negative affects version of PANAS (nine items), the reliability coefficient was .79 and the explained variance was 16.2%. For the positive affects version of PANAS (seven items), the reliability was .70 and explained variance was 8.5% (Cardoso & Ferreira, 2009). …”
Section: Instrumentsmentioning
confidence: 97%
See 1 more Smart Citation
“…For the negative affects version of PANAS (nine items), the reliability coefficient was .79 and the explained variance was 16.2%. For the positive affects version of PANAS (seven items), the reliability was .70 and explained variance was 8.5% (Cardoso & Ferreira, 2009). …”
Section: Instrumentsmentioning
confidence: 97%
“…Subjective Well-Being Scale (Cardoso & Ferreira, 2009). This instrument measured subjective well-being, with adaptation of the Satisfaction with Life Scale by Lawton (1975) and Neugarten, Havighurste Tobin (1961) and the Positive and Negative Affect Schedule (PANAS) by Watson, Clark and Tellegen (1988).…”
Section: Instrumentsmentioning
confidence: 99%
“…A RNO engloba os hábitos e comportamentos religiosos que podem ocorrer fora do ambiente e do contexto de uma instituição ou organização religiosa, sem a forma das liturgias estabelecidas por estas. Ao contrário da RO, não depende necessariamente da interação com outras pessoas, podendo manifestar-se individualmente ou em pequenos grupos familiares e informais 24 . Encontra exemplos nas orações, na leitura da Bíblia ou de outros textos religiosos e na audiência a programas religiosos da televisão ou do rádio.…”
Section: Introductionunclassified
“…However, the literature has shown that quality of life has long been assessed through economic and sociodemographic indicators, that is, objective indicators that can only depict the living conditions of individuals; the social indicators, including criteria for personal judgment of well-being and satisfaction with life, have just been incorporated into studies on quality of life [12].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the subjective well-being refers to the reasons why personal experiences take place in a positive way, which is why it is based both on cognitive judgment and affective reactions resulting from these experiences [12,13].…”
Section: Introductionmentioning
confidence: 99%